From Zero to Senior Researcher: A Complete Guide to Scientific Writing of Clinical Case Reports. The Secrets of Case Reports Editors Don’t Want You to Know - Ribeiro Junior, Howard Lopes (Brazilian Journal of Case Reports, 2023)
A clinical case report is a type of scientific article that describes the experience of one or more healthcare professionals with a patient or a group of patients presenting with a rare, unusual, complex, innovative, or educational clinical condition. The aim of a clinical case report is to share knowledge, evidence, hypotheses, lessons, and challenges regarding the diagnosis, treatment, prognosis, prevention, or etiology of a disease or health problem. The clinical case report is one of the oldest and most popular forms of scientific publication in the health field. It plays an important role in advancing science, clinical practice, and medical education, as it allows for the recording and dissemination of cases that may contribute to the development of new hypotheses, theories, methods, techniques, interventions, or recommendations. However, writing and publishing a clinical case report is not an easy task. It requires care, rigor, ethics, and quality in preparing the text, selecting the journal, submitting the manuscript, and disseminating the article. There are several types and characteristics of clinical case reports that must be matched to the purpose, audience, and context of the case. There are also numerous standards, guidelines, instructions, and criteria that must be followed to ensure the reliability, validity, originality, and relevance of the clinical case report. In this book, you will learn how to write and publish a clinical case report efficiently, effectively, and ethically. You will understand the concepts, steps, tips, and tools that will help you transform your clinical experience into a quality scientific article. You will discover how to choose a relevant clinical case, how to collect and organize data, how to conduct a literature review, how to structure the text, how to follow ethical standards and journal guidelines, how to write clearly, objectively, and attractively, how to use figures, tables, and references, how to avoid common mistakes, how to revise and edit the text, how to choose an appropriate journal, how to prepare and submit the manuscript, how to handle reviewers’ comments, how to make revisions, and how to disseminate the article. By the end of this book, you will have acquired the knowledge and skills needed to write and publish a clinical case report that contributes to the advancement of science, clinical practice, and medical education. ISBN: 978-65-981870-1-9 (PDF)